Pengaruh Pelayanan Administrasi Terhadap Kepuasan Pasien Di RSUD. Pasar Rebo - Samsudin (CV ODIS, 2021)
This study aims to find out and analyze the effect of the quality of administrative services on patient satisfaction of Rebo Market Hospital. The sample taken was as much as 35% of the population, which is 29% x 350 = 101.5 people (rounded to 100 people). Using simple regression analysis, resulting in Quality of Administrative Services has a significant effect on Inpatient Satisfaction. The regression coefficient value of administrative service quality of 0.740 indicates that if the quality of Administrative services is improved by one unit then inpatient satisfaction will increase by 74%.